Efficacy and safety of sofosbuvir plus ribavirin in treatment-naive chronic hepatitis c genotype 3 patients of South Punjab, Pakistan - Ali, Qazi Masroor; Raza, Syed Hashim; Imran, Ali; Anjum, Saba; Masroor, Maria (International Journal of Research in Medical Sciences, 2020)
Background: To evaluate the efficacy and safety of sofosbuvir (SOF) plus ribavirin (RIB) in naive patients with chronic HCV genotype 3. The study design was open label, quasi experimental study. The study was conducted at Medical Outpatient Department of Medical Unit-1, Bahawal Victoria Hospital, affiliated with Quaid e Azam Medical College (QAMC), Bahawalpur, from April 2016 to June 2019. Methods: A total of 627 treatment-naive patients, aged above 18 years, with chronic Hepatitis C virus (HCV) genotype 3 infection were enrolled. SOF as 400 mg once a day plus weight-based RIB (1000 mg/day <75 kg and 1200 mg/day >75 kg) was given to all the study participants for 24 weeks. Qualitative polymerase chain reaction (PCR) for HCV ribonucleic acid (RNA) were done at 4 weeks to note the rapid virological response (RVR) whereas end of treatment response (ETR) was recorded at 24 weeks and sustained virological response (SVR) was noted 3 months after completion of treatment. Results: By 4th week, PCR of 524 (83.6%) patients was available, out of which, 492 (93.9%) had undetectable HCV RNA. By the end of treatment (24 weeks), PCR of 401 (64.0%) patients was available, out of which, 393 (98.0%) had undetectable HCV RNA. Data of 291 (46.4%) patients was available for SVR, 274 (94.1%) had undetectable HCV RNA. Weakness and fatigue turned out to be the commonest side effects, observed in 236 (37.6%) patients. Conclusions: Sofosbuvir was found to have good efficacy and safety in the local population of South Punjab having treatment-naïve chronic HCV genotype 3 infection.